Real Time Health Monitoring System Through Iot Using Sensors - Pavithra S; Shanmuga Priya G; Supraja A; Dr.T.A.Anusudha (Elementary Education Online, 2023)
Cardiovascular Diseases is one of the major causes of death in the world and COVID-19 is threatening the wholeworld with its high mortality rate in recent days. COVID-19 is a disease caused bycorona virus called SARS-CoV-2. People aged 60 and above and those with underlying medical conditions like cardiovascular disease, chronic respiratory disease are more likely to develop serious illness through COVID-19. The World Health Organization report shows that 17.9 million people die every year from cardiovascular diseases, an estimated 31% of all deaths worldwide and by 2030, cardiovascular diseases will be the main cause of death accounting for more than 35%. In this project, we intend to save people by giving them an alert message and sending mail to the concerned doctors using their android phone and also monitor the individual’s body temperature and SpO2 level to detect any abnormalities in an individual relating to these biological factors. The Arduino UNO R3, LCD display, heartbeat sensor, temperature sensor, SpO2 sensor, ESP8266 Wi-Fi module, LM35 sensor, LM358 Op-Amp and other electronic devices coupled together through an android app will help to accomplish a better way of the health monitoring system.